Self-assembly Ag nanoparticle monolayer film as SERS Substrate for pesticide detection - Zhang, Li (Applied surface science, 2013)
[Display omitted] ► A simple self-assembled method was used to fabricate ordered Ag nanosized film. ► The assembled ordered Ag nanosized film was monolayer, and the ordered film with large area. ► The assembled monolayer film with excellent Raman enhancement and reproducibility, which has been used to detect pesticide. A self-assembled protocol is introduced to provide effective platforms for the fabrication of ordered Ag nanosized monolayer film. The assembled Ag nanosized monolayer film was characterized using scanning electronic microscopy and surface-enhanced Raman scattering (SERS). The results show that the assembled SERS substrate own excellent Raman enhancement and reproducibility. The synthesized SERS-active substrate was further used to detect methyl-parathion, and the limitation of detection can reach 10−7M.